2020
DOI: 10.3389/fnins.2020.00152
|View full text |Cite
|
Sign up to set email alerts
|

Left Prefrontal Cortex Supports the Recognition of Meaningful Patterns in Ambiguous Stimuli

Abstract: Processing of ambiguous visual stimuli has been associated with an increased activation of the left lateral prefrontal cortex (PFC) in neuroimaging studies. Nevertheless, the functional role of prefrontal activity in this process is not fully understood. In this experiment we asked participants to evaluate ambiguous inkblots from the Rorschach test, while stimulating the left lateral PFC using excitatory anodal transcranial direct current stimulation (tDCS). In addition, visual insight ability was assessed as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 57 publications
1
7
0
Order By: Relevance
“…This is not surprising, assuming that the process of reality testing is expected to be occurring through the overall processes during the administration of the Rorschach. The laterality of the prefrontal activation associated with frequent responses is consistent with the study that showed that stimulating the left prefrontal cortex with excitatory anodal transcranial direct current stimulation increased the number of meaningful responses to a Rorschach figure (Bartel et al, 2020). It might be possible to say that the fronto-temporo-occipital network revealed here is the neural substrate for the "Rorschach Perceptual Accuracy" factor extracted by Zillmer and Perry (1996).…”
Section: Form Qualitysupporting
confidence: 89%
“…This is not surprising, assuming that the process of reality testing is expected to be occurring through the overall processes during the administration of the Rorschach. The laterality of the prefrontal activation associated with frequent responses is consistent with the study that showed that stimulating the left prefrontal cortex with excitatory anodal transcranial direct current stimulation increased the number of meaningful responses to a Rorschach figure (Bartel et al, 2020). It might be possible to say that the fronto-temporo-occipital network revealed here is the neural substrate for the "Rorschach Perceptual Accuracy" factor extracted by Zillmer and Perry (1996).…”
Section: Form Qualitysupporting
confidence: 89%
“…Psychologically, the first study suggests that conventional perceptions are associated with the perception of obscured or imprecisely rendered objects and the retrieval of visual content to potentially match it (bilateral occipitotemporal activation) while engaging semantic categorization via thoughts and ideas about those perceptions (left anterior prefrontal activation; see also Bartel et al, 2020). Conversely, unique perceptions are associated with processes that link perception to visceral emotional responses, likely of an autobiographically relevant nature (right temporal pole activation).…”
Section: Fq Variablesmentioning
confidence: 99%
“…The left prefrontal cortex is often thought to play a role in the classification of words or pictures into semantic categories ( Gabrieli et al, 1998 ). Recent research has suggested that the left prefrontal cortex plays a role in processing ambiguous visual information and object recognition through its involvement in storing visual and semantic information ( Bartel et al, 2020 ). Combined with the role of the prefrontal cortex in executive functioning, any potential impairment to cerebral oxygenation may contribute to the behavioural and cognitive declines that are often reported in individuals with a history of multiple concussions ( Guskiewicz et al, 2005 ; Iverson et al, 2012 ; Montenigro et al, 2016 ).…”
Section: Discussionmentioning
confidence: 99%